Plant and Revitalize or Create and Recreate? A discursive textual analysis of PAMI and the proposed missionary church - Ricardo Ramlow, Rodomar; Ricardo Ramlov, Romildo (Vox Scripturae - Revista Teológica Internacional, 2025)
Understanding the concept of a missional church is directly linked to a church’s ability to understand its task in planting churches or the need to revitalize its ecclesiology from a missionary hermeneutic. Being or becoming a missional church is directly related to the ability to be faithful to the gospel and relevant to the culture. The main characteristic of a missional church is that it revitalizes itself to plant churches and plant churches to revitalize. Already the main characteristics of a declining church are seen in its omission to the gospel and its difficulty of cultural contextualization. This work seeks to understand the relationship between Planting and Revitalizing Churches from the missional church movement compared to Creating and Rebuilding Communities of the Missionary Action Plan of the IECLB - PAMI. In terms of definitions and contemporary understanding of the missional church, the terminology on Recreating and Creating Communities (Missionary Action Plan of the IECLB - PAMI) and Revitalizing and Planting Churches (literature available since 2000) are analyzed through Discursive Textual Analysis. Although the IECLB has been declining in recent years, PAMI, which aims to recreate and create communities, presents a total linguistic harmony with the discourse on planting and revitalization based on the understanding of the missional concept. The challenge of the IECLB, therefore, would be to rethink the nature of the church and the mission in a missionary perspective (Missio Dei), seeking paradigmatic changes in its ecclesiology and missiology. More than a tool for strategic planning, PAMI should assist IECLB members in understanding the concept of the missional church and, consequently, be an incarnational church committed to the gospel and sensitive to the cultural context.